1970
DOI: 10.1111/j.1365-3180.1970.tb00919.x
|View full text |Cite
|
Sign up to set email alerts
|

The Degradation of Triazine and Uracil Herbicides in Soil*

Abstract: Summary. The rates of degradation of three triazine and two uracil herbicides were followed at 13·2 and 31·2°C in one soil. Soil was treated with 8 ppm of 2‐chloro‐4‐ethyl‐amino‐6‐isopropylamino‐1,3,5‐triazine (atrazine), 2‐chloro‐4,6‐bisethylamino‐1,3,5‐triazine (simazine), 2‐mcthylthio‐4‐ethylamino‐6‐isopropylamino‐1,3,5‐triazine (ametryne), 3‐sec‐butyl‐5‐bromo‐6‐methyluracil (bromacil) and 3‐tert‐butyl‐5‐chloro‐6‐methyluracil (terbacil) and monthly samples analysed chemically to determine the amounts remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
1

Year Published

1970
1970
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 14 publications
2
26
1
1
Order By: Relevance
“…The same results were also observed 84 days after pendimethalin application (P = 0.056). Similar results were presented by Zimdahl and Clark (1984). They found no effect of pendimethalin dose (1.2 and 2.4 kg/ha) on its half-life calculated 45 days after pendimethalin application.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The same results were also observed 84 days after pendimethalin application (P = 0.056). Similar results were presented by Zimdahl and Clark (1984). They found no effect of pendimethalin dose (1.2 and 2.4 kg/ha) on its half-life calculated 45 days after pendimethalin application.…”
Section: Resultssupporting
confidence: 78%
“…Other factors such as cultivation practices, mode of doi: 10.17221/226/2015-SWR (Piutti et al 2002), and herbicide incorporation into the soil after its application (Talbert & Press 1997), or application of Fenton's reagent (Miller et al 1996) can affect the pendimethalin half-life. The effect of soil moisture and soil temperature was described by Zimdahl and Clark (1984). They described increased pendimethalin degradation with the increase of both soil moisture and temperature, and they suggested that soil type may have less influence than temperature and soil moisture.…”
mentioning
confidence: 99%
“…The degradation product of metolachlor, 2-hydroxy-N-(2-ethyl-6-methylphenyl)-N-(hydroxyprop-2-yl) acetamide, was prepared as follows: i) KI [10], and Vischetti and Businelli [9]. The influence of temperature and soil moisture on degradation was evident.…”
Section: Identification Of Degradation Productsmentioning
confidence: 99%
“…Biodegradation is the primary means of metolachlor dissipation in soil [11][12][13][14]. Factors that influence microbial activity, especially soil temperature and moisture content, in turn influence the persistence of metolachlor [13,15]. Pesticides may also affect soil microbial activity depending on the rate of application, persistence, availability, and toxicity of the compound.…”
Section: Introductionmentioning
confidence: 99%